Validation of low‐coverage whole‐genome sequencing for mitochondrial DNA variants suggests mitochondrial DNA as a genetic cause of preterm birth. Issue 12 (8th September 2021) - Yang, Zeyu; Slone, Jesse; Wang, Xinjian; Zhan, Jack; Huang, Yongbo; Namjou, Bahram; Kaufman, Kenneth M.; Pauciulo, Michael; Harley, John B.; Muglia, Louis J.; Chepelev, Iouri; Huang, Taosheng
Abstract: Preterm birth (PTB), or birth that occurs earlier than 37 weeks of gestational age, is a major contributor to infant mortality and neonatal hospitalization. Mutations in the mitochondrial genome (mtDNA) have been linked to various rare mitochondrial disorders and may be a contributing factor in PTB given that maternal genetic factors have been strongly linked to PTB. However, to date, no study has found a conclusive connection between a particular mtDNA variant and PTB. Given the high mtDNA copy number per cell, an automated pipeline was developed for detecting mtDNA variants using low‐coverage whole‐genome sequencing (lcWGS) data. The pipeline was first validated against samples of known heteroplasmy, and then applied to 929 samples from a PTB cohort from diverse ethnic backgrounds with an average gestational age of 27.18 weeks (range: 21–30). Our new pipeline successfully identified haplogroups and a large number of mtDNA variants in this large PTB cohort, including 8 samples carrying known pathogenic variants and 47 samples carrying rare mtDNA variants. These results confirm that lcWGS can be utilized to reliably identify mtDNA variants. These mtDNA variants may make a contribution toward preterm birth in a small proportion of live births. Abstract : Maternal genetic factors have been strongly linked to preterm birth (PTB). While mitochondrial DNA (mtDNA) has been proposed as a possible maternal factor that may contribute to preterm birth, no study has conclusively linked an mtDNA variant to PTB. As shown here, we have developed a new automated pipeline for mining mtDNA variants using low‐pass whole genome sequencing (lcWGS) data, and applied it to 929 preterm lcWGS samples to elucidate the contribution of mtDNA to preterm birth.